Improving Anxiety Emotion Regulation Abilities Based on Cognitive Behavioral Therapy in Children With Stuttering - Oktarian Nisa Wulandari; Endang Widyorini (Green Publisher, 2025)
Anxiety is a condition in which a person experiences excessive fear, worry, or nervousness that often triggers the fight-oor-flight response. The presence of anxiety can worsen pre-existing physical conditions, such as stuttering in children. Excessive anxiety can worsen stuttering symptoms, which are characterized by inhibition of words when speaking. Anxiety in children can be overcome, one effective method is cognitive behavioral therapy (CBT). This study aims to test the effectiveness of CBT-based interventions in improving anxious emotion regulation in children during middle childhood. This study used a mixed method with a single case design, combining quantitative and qualitative approaches. Data were collected using the Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA), the Social Anxiety Scale for Adolescents (SAS-A), and interviews with subjects and their parents. The participant was a 9-year-old boy who was identified as having poor emotion regulation skills and prominent anxiety levels, based on the assessment results. The subject underwent a CBT-based intervention for 11 sessions targeting anxiety-related emotion regulation. The results showed that the intervention effectively improved subjects’ ability to manage anxious emotions, as evidenced by reduced frequency, avoidance behavior, and duration of stuttering episodes during anxiety-provoking situations.